Masking for Trouble. - Vallere, Diane (Vallere, Diane. Costume shop mysteries., 2016)
Halloween conjures up big business for Margo Tamblyn's costume shop, Disguise DeLimit, but this year, the holiday comes knocking with serious trouble. Venture capitalist Paul Haverford plans to rezone historic downtown into a glitzy commercial area which would push out local business. Margo is set on saving her family's store, especially after a nasty run-in with the chain-store tycoon, but after Haverford's body is discovered during a spooky party at the derelict Alexandria Hotel, Margo finds herself dressed as the police's prime suspect.